Differences between expert and novice gymnasts performance of a counter movement forward in flight on uneven bars - Huchez, A.; Haering, D.; Holvoet, P.; Barbier, F.; Begon, M. (Science of Gymnastics Journal, 2016)
This study investigated the different strategies exhibited by expert and novice gymnasts in counter movement forward in flight on uneven bars. Eleven gymnasts performed three trials connected with a kip to support. The gymnasts were divided into two groups according to their ability to connect: six able (termed as experts) versus five non-able (novices). The 3D motion data were collected at 250 Hz. Biomechanical parameters were computed at release (release state and angular momentum), during aerial phase (duration, minimum value of the moment of inertia) and at regrasp (total duration and rotation angle). Robustness of the release state was also compared. Significant differences were found between groups in the three phases. The novice gymnasts performed as robustly as expert gymnasts but less efficiently because they released the low bar before their centre of mass passed the horizontal, with a lower vertical velocity, resulting in a lower and shorter aerial phase. They also had a larger minimum moment of inertia in flight. Coaches could help novice gymnasts to decrease their dependency on their robust technique by improving the release angle. Exercises, which may allow novice gymnasts to exceed the threshold of a 90° rotation angle at release are suggested.